Smartphone‐compatible, CRISPR‐based platforms for sensitive detection of acute hepatopancreatic necrosis disease in shrimp - Punyaporn Naranitus; Praphutson Aiamsa‐at; Thanwarat Sukonta; Pimkhuan Hannanta‐anan; Thawatchai Chaijarasphong (Journal of Fish Diseases, 2022)
Acute Hepatopancreatic Necrosis Disease (AHPND), caused by bacterial isolates expressing PirAB binary toxins, represents the severest and most economically destructive disease affecting penaeid shrimp. Its rapid disease progression and associated massive mortalities call for vigilant monitoring and early diagnosis, but molecular detection methods that simultaneously satisfy the requirements of sensitivity, specificity, and portability are still scarce. In this work, the CRISPR-Cas12a technology was harnessed for the development of two fluorescent assays compatible with naked-eye visualization. The first assay, AP4-Cas12a, was based on the OIE-recommended AP4 two-tubed nested PCR method and was designed to bypass the time-consuming and potentially hazardous agarose gel electrophoresis step. Using AP4-Cas12a, the detection limit of 10 copies per reaction could be achieved within less than 30 minutes post-PCR. The second assay, RPA-Cas12a, utilized recombinase polymerase amplification (RPA) to rapidly and isothermally amplify the target DNA, followed by amplicon detection by Cas12a, resulting in a protocol that can be completed in less than an hour at a constant temperature of 37°C. The detection limit of RPA-Cas12a is 100 copies of plasmid DNA or 100 fg of bacterial genomic DNA per reaction. Importantly, we validated that both assays are compatible with a previously reported smartphone-based device for facile visualization of fluorescence, thereby providing an affordable option that requires less consumables than lateral flow detection. Using this portable device for readouts, the AP4-Cas12a and RPA-Cas12a methods showed excellent concordance with the AP4-agarose gel electrophoresis approach in the evaluation of clinical samples. Therefore, the developed Cas12a assays have the potential to streamline both in-laboratory and onsite diagnosis of AHPND.
Keywords: CRISPR and Genetic Engineering; Innovation and Socioeconomic Development; Mosquito-borne diseases and control